Pengembangan E-Modul PJOK Berbasis Pembelajaran SAVI Pada Materi Lari Jarak Pendek Untuk Meningkatkan Hasil Belajar Siswa: Pengembangan E-Modul PJOK Berbasis Pembelajaran SAVI Pada Materi Lari Jarak Pendek Untuk Meningkatkan Hasil Belajar Siswa - Bayu Wahyudi; Dwi Yullianti; Frans Nurseto Subekti (WACANA AKADEMIKA: Majalah Ilmiah Kependidikan, 2022)
The purpose of this study was to develop an E-module based on SAVI learning on short-distance runningmaterial and to test the effectiveness and efficiency of the learning process using the developed learning designproduct. This type of research is R & D using Sugiyono's modification development which consists of 6 stagesincluding: (1) potential and problems, (2) data collection, (3) product design, (4) product validation, (5) productimprovement, and (6) product trial. The research subject is class X Mathematics and Natural Sciences at SMANegeri 1 Abung Tengah TP 2021/2022 with data collection techniques of observation, interviews,questionnaires, tests and documentation. Data analysis techniques include analysis of evaluation instruments,expert validation analysis, analysis of learning outcomes, efficiency and attractiveness analysis. The researchresults obtained include: (1) The process of developing validation results by experts stating that it is very validand feasible to use; (2) The percentage result of the average increase (index gain) of student learning outcomesclassically is 76% in the good category with effective criteria; (3) Time efficiency, cost efficiency and learningefficiency using the PJOK e-module based on SAVI learning on short-distance running material to improvestudent learning outcomes by 85.76% in good category with efficient criteria; and (4) the results of the assessmentof teacher and student responses that the product of developing the PJOK e-module based on SAVI learning onshort-distance running material to improve student learning outcomes obtained very interesting results.